The old and the oldest-old : Do they have different perspectives on adjustment to aging? - von Humboldt, Sofia (2015)
Background: Older adults experience varying challenges in old age. This study aims to explore the indicators of adjustment to aging (AtA) and to examine the potential explanatory mechanisms of a correlational model for AtA for the old and oldest-old adults. Methods: This qualitative study comprised demographics and semistructured interviews. Complete information on 152 older adults aged between 75 years and 102 years (mean ¼ 83.76 years; standard deviation ¼ 6.458). Data was subjected to content analysis. The correlational model of indicators of AtA was analyzed using a multiple correspondence analysis. Results: “Occupation and achievement” was the most mentioned indicator of AtA by the old participants (17.7%), whereas “existential meaning and spirituality” was the most verbalized indicator of AtA for the oldest-old participants (16.9%). AtA was explained by a three-factor model for each age group. For the old participants, the largest factor “occupational and social focus” accounted for 33.6% of total variance, whereas for the oldest-old participants, “spirituality and health focus” represented 33.5% of total variance. Conclusion: The outcomes presented in this paper stressed the varied perspectives concerning AtA, contoured in two different models, and the need of considering these when designing and implementing programs in health care for the old and the oldest-old.